Signalling pathways in succinate dehydrogenase B‐associated renal carcinoma. Issue 4 (18th November 2013) - Fleming, Stewart; Mayer, Nick J; Vlatkovic, Ljiljana J; McLean, Joanne; McConachie, Michelle; Baty, David
<x xml:space="preserve">Abstract</x> Aims Renal tumours have recently been described in association with mutations in the gene encoding the B subunit of succinate dehydrogenase, a mitochondrial Krebs cycle and electron transport chain enzyme (SDHB‐associated renal cell carcinomas). The aim of this study was to investigate the roles of different signalling pathways in the pathogenesis of these tumours. Methods and results We used immunohistochemistry and antibodies against phospho‐specific epitopes to examine the activity of three potential signalling pathways in tumour cells of three genetically confirmed cases of SDHB‐associated renal cell carcinomas. We found no evidence supporting a role for either the mTOR [p‐mTOR (Ser2448), p‐S6 riboprotein (Ser235/236)] or hypoxia‐inducible (carbonic anhydrase 9 and EGFR) pathways. However, there was immunohistochemical reactivity for phosphorylated AMP‐dependent kinase (p‐AMPK Thr172) and glycogen synthase kinase 3 (GSK3) phosphorylation (p‐GSK3 Ser12), and nuclear expression of cyclin D1. Conclusions We suggest that these tumours may arise through a mechanism involving ATP depletion, activation of AMPK, and induction of cyclin D1, and that this may be a unique pathway of tumour development that has the potential for therapeutic intervention in these rare tumours.